Quantum Diamond Microscopy of Individual Vaterite Microspheres Containing Magnetite Nanoparticles - Mona Jani; Hani Barhum; Janis Alnis; Mohammad Attrash; Tamara Amro; Nir Bar-Gill; Toms Salgals; Pavel Ginzburg; Ilja Fescenko (Nanomaterials)
Biocompatible vaterite microspheres, renowned for their porous structure, are promising carriers for magnetic nanoparticles (MNPs) in biomedical applications such as targeted drug delivery and diagnostic imaging. Precise control over the magnetic moment of individual microspheres is crucial for these applications. This study employs widefield quantum diamond microscopy to map the stray magnetic fields of individual vaterite microspheres (3–10 μm) loaded with Fe3O4 MNPs of varying sizes (5 nm, 10 nm, and 20 nm). By analyzing over 35 microspheres under a 222 mT external magnetizing field, we measured peak-to-peak stray field amplitudes of 41 ± 1 μT for 5 nm and 10 nm superparamagnetic MNPs, reflecting their comparable magnetic response, and 12 ± 1 μT for 20 nm ferrimagnetic MNPs, due to distinct magnetization behavior. Finite-element simulations confirm variations in MNP distribution and magnetization uniformity within the vaterite matrix, with each microsphere encapsulating thousands of MNPs to generate its magnetization. This high-resolution magnetic imaging approach yields critical insights into MNP-loaded vaterite, enabling optimized synthesis and magnetically controlled systems for precision therapies and diagnostics.